Serum and Fecal Markers of Intestinal Inflammation and Intestinal Barrier Permeability Are Elevated in Parkinson’s Disease - Dumitrescu, Laura; Marta, Daciana; Dănău, Adela; Lefter, Antonia; Tulbă, Delia; Cozma, Liviu; Manole, Emilia; Gherghiceanu, Mihaela; Ceafalan, Laura Cristina; Popescu, Bogdan Ovidiu (Frontiers in Neuroscience, 2021)
Parkinson’s disease (PD) is characterized by alpha-synuclein misfolding with subsequent intraneuronal amyloid formation and accumulation, low grade neuroinflammatory changes, and selective neurodegeneration. Available evidence suggests that the pathology usually begins in the gut and olfactory mucosa, spreading to the brain via the vagus and olfactory nerves, by a prion-like mechanism. A causal relationship has not been established, but gut dysbiosis is prevalent in PD and may lead to intestinal inflammation and barrier dysfunction. Additionally, epidemiological data indicate a link between inflammatory bowel diseases and PD. Calprotectin and zonulin are markers of intestinal inflammation and barrier permeability, respectively. We evaluated their serum and fecal levels in 22 patients with sporadic PD and 16 unmatched healthy controls. Mean calprotectin was higher in PD, both in serum (14.26 mcg/ml ± 4.50 vs. 5.94 mcg/ml ± 3.80, p = 0.0125) and stool (164.54 mcg/g ± 54.19 vs. 56.19 mcg/g ± 35.88, p = 0.0048). Mean zonulin was also higher in PD serum (26.69 ng/ml ± 3.55 vs. 19.43 ng/ml ± 2.56, p = 0.0046) and stool (100.19 ng/ml ± 28.25 vs. 37.3 ng/ml ± 13.26, p = 0.0012). Calprotectin was above the upper reference limit in 19 PD serums and 6 controls (OR = 10.56, 95% CI = 2.17–51.42, p = 0.0025) and in 20 PD stool samples and 4 controls (OR = 30, 95% CI = 4.75–189.30, p = 0.000045). Increased zonulin was found only in the stool samples of 8 PD patients. Despite the small sample size, our findings are robust, complementing and supporting other recently published results. The relation between serum and fecal calprotectin and zonulin levels and sporadic PD warrants further investigation in larger cohorts.